Rough Fe3O4/gold nanostructure enhanced fluorescence of quantum dots for Salmonella typhimurium detection in cabbage - Abdulhakeem Alzahrani; Tawfiq Alsulami; Ahmad Mohammad Salamatullah; Hind Saeed Alzahrani (Journal of King Saud University: Science, 2024)
Salmonella typhimurium (S. typhimurium) is a leading biological factor of foodborne diseases. A sensitive detection for S. typhimurium is crucial to controlling fresh vegetable-related outbreaks. Here, fluorescence-based S. typhimurium detection in fresh cabbage samples has been reported which capitalizes on the plasmon-exciton interaction between non-spherical gold nanoparticles-covered iron oxide nanoparticles (Fe3O4@Au NPs) and gold quantum dots (Au QDs). Firstly, new synthesis methods for non-spherical Fe3O4@Au NPs and Au QDs are reported. Then, a two-fold emission enhancement and shortening of the lifetime were achieved from urchin-like NPs compared with those of spherical NPs. This finding was utilized for the detection of S. typhimurium. Results revealed that the changes in fluorescence emission were linearly correlated with the concentration of S. typhimurium within the range of 100–1000 colony forming unit per milliliter (CFU mL−1) and the limit of detection was 32 CFU mL−1 in fresh cabbage.